KARAKTERISTIK UNJUK KERJA PUMP AS TURBINE (PAT) MENGGUNAKAN SATU POMPA HISAP UNTUK PEMBANGKIT LISTRIK - Lubis, Sudirman; Siregar, Munawar Alfansury (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Water energy is still one of the main energy sources used to generate electrical energy so that it can be widely used. Although it still has shortcomings, the environmental impact caused by hydropower is relatively lower in risk compared to diesel power plants or nuclear power plants. Pump as turbine (PAT) is suitable for use as an applied technology to meet the needs of electrical energy, especially those who live in areas with many rivers. This research on pump as a turbine aims to determine the performance characteristics of the pump as a turbine. The tools used in this research are: pump as a turbine, source pump, alternator, flow meter, pipes, measuring instruments, and others. The research begins by designing and assembling pipes to drain water from the circulation bath to the source pump, then enter the pump as a turbine and the water that comes out of the pump as a turbine is flowed into the basin. After everything is installed, the initial experiment is carried out, then the implementation stage and data collection are carried out. In this study, the data taken are: rotation on the turbine shaft, the voltage and current generated by each loading, and the flow of water entering through the flow meter to the turbine per measured unit of time. From the research results, the highest efficiency is 0.0075% at discharge = 0.000174 m³ / sec, Head = 0.224 m and Nq = 51.25 rpm and produces an output power of 2.556 Watts.